The Use of Market Orientation As an Effective Approach in Winning and Sustaining Market - Asmai Ishak (Sinergi: Kajian Bisnis dan Manajemen, 2008)
When Asia becomes an integrated market, it means two things for companies op-erating in it. Firstly, they will have much bigger market, but secondly they will have many new competitors to win the market. The question is, especially for Indonesian companies, are they ready to compete in such more global market? This simple question arises from the reality that most of Indonesian companies are not able to compete with foreign ones. The main reason for this incompetence is that many Indonesian managers tend to ignore customers’ needs, and presume that the market will absorb whatever they produce. In current business environment, information technology enables consumers to be well informed, and to select what they want. Only satisfying customer is not enough in today’s business environment. This paper discusses the importance of the adoption of market orientation for Indonesian companies to face the en-vironmental changes resulting from Asian as an integrated market.Keywords: market orientation, integrated market, competition